The directive function, key element for the development of educational institutions - Batanaz Palomares, Luis (Avances en Supervisión Educativa, 2006)
This article analyses the fundamentals of educational management practice in Spain. Starting from the conception of educational management as an aspect of vital importance for the educational system, a review is undertaken on the base of educational research available at present to achieve a suitable answer to the problem. The author’s outlook upon the present state of the problem focuses on the need of professionalizing the educational management of schools for their pedagogical vivification. In support of this idea, the practice of educational management must be understood as a duty to be performed free from political factors and direct political control.